Extending nearly Zero-Energy Buildings Load Matching Improvement to Community-Level - Lopes, Rui Miguel Amaral (2018)
The nearly Zero-Energy Building (nZEB) concept is foreseen as a reference for the future of the European building stock. While several factors contribute to the introduction of legal instruments that promote a fast adoption of these buildings (e.g. energy efficiency), their relationship with Low Voltage distribution Grids (LVGs) is far more complex than the one of the regular buildings. In order to improve the grid interaction of nZEBs in particular, and of regular buildings equipped with distributed generation systems in general, Load Matching (LM) improvement incentives are being promoted worldwide. The literature shows that the existing LM improvement measures, that use the Energy Flexibility offered by controllable electricity demand devices, are only conducted at individual buildings (i.e. Building-Level) without taking into consideration the demand and on-site generation profiles of other buildings. Therefore, the first main objective of this research work refers to the assessment of impacts introduced by Building-Level LM improvement measures on existing LVGs. In order to improve the benefits offered to LVG operators and building owners (when compared to the existing Building-Level LM improvement measures), the second main objective concerns the development of a new LM improvement approach. For this purpose, the Cooperative Net-Zero Energy Community concept is introduced, extending the LM improvement to the Community- Level. A neighborhood made up of 33 buildings is considered to conduct the necessary experiments, where the benefits offered to LVG operators are quantified by three important Performance Indictors and the benefits offered to building owners are quantified by the respective electricity bills. The obtained results show that Building-Level LM improvement measures can be harmful to LVG operators when large amounts of controllable electricity demand are shifted to coincident periods. The conducted experiments also show that the proposed Cooperative Net-Zero Energy Community concept improves the benefits offered to LVG operators and building owners.